NOTA SOBRE UN NUEVO HALLAZGO DE LITO DISCOIDAL EN LA ZONA DE PALI-AIKE, MAGALLANES - Huidobro, Consuelo; Martin, Fabiana (Magallania, 2025)
A morphological, technical and traceological description of a discoidal stone from a private collection, collected near the site of Cueva Fell, is presented. The results are compared with the information available for similar artifacts in Patagonia and Pampa.